2017
DOI: 10.1103/physrevlett.118.081602
|View full text |Cite
|
Sign up to set email alerts
|

Construction of all N=4 conformal supergravities

Abstract: All N = 4 conformal supergravities in four space-time dimensions are constructed. These are the only N = 4 supergravity theories whose actions are invariant under off-shell supersymmetry. They are encoded in terms of a holomorphic function that is homogeneous of zeroth degree in scalar fields that parametrize an SU(1, 1)/U(1) coset space. When this function equals a constant the Lagrangian is invariant under continuous SU (1, 1) transformations. The construction of these higher-derivative invariants also opens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 31 publications
(53 reference statements)
0
66
0
Order By: Relevance
“…Recently Tseytlin considered general non-minimal N = 4 conformal supergravities, and concluded that they are free of conformal anomalies given that four vector multiplets are added to the spectrum [123]; thus agreeing with the analysis of the minimal theory [124][125][126]. A complete bosonic action for all N = 4 non-minimal conformal supergravity theories -parametrized by a free function -has been proposed by Butter, Ciceri, de Wit and Sahoo [127]. We confirm in this work, by direct calculation of amplitudes from both the double copy and the action, that the Lagrangian of the Berkovits-Witten theory is given by a simple choice of the free function.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…Recently Tseytlin considered general non-minimal N = 4 conformal supergravities, and concluded that they are free of conformal anomalies given that four vector multiplets are added to the spectrum [123]; thus agreeing with the analysis of the minimal theory [124][125][126]. A complete bosonic action for all N = 4 non-minimal conformal supergravity theories -parametrized by a free function -has been proposed by Butter, Ciceri, de Wit and Sahoo [127]. We confirm in this work, by direct calculation of amplitudes from both the double copy and the action, that the Lagrangian of the Berkovits-Witten theory is given by a simple choice of the free function.…”
Section: Introductionmentioning
confidence: 72%
“…In particular, we have identified a non-minimal N = 4 conformal supergravity Lagrangian whose physical planewave amplitudes are those of the Berkovits-Witten theory [12]. This theory turns out to be a simple case of the infinite class of non-minimal Lagrangians derived by Butter, de Wit, Ciceri and Sahoo [127]. The tree amplitudes are predicted by a double copy between N = 4 super-Yang-Mills and a (DF ) 2 theory, where the latter gauge theory was introduced by Nohle and one of the present authors in ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conformal superspace approach is at the heart of the construction of all N = 4 conformal supergravity theories in four dimensions[103].…”
mentioning
confidence: 99%